2001
DOI: 10.1007/s002030100254
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acids in the leader peptide of Methanococcus voltae preflagellin that are important in posttranslational processing

Abstract: Archaeal flagellins are made initially as preproteins with short, positively charged leader peptides. Analysis of all available archaeal preflagellin sequences indicates that the -1 position is always held by a glycine while the -2 and -3 positions are almost always held by charged amino acids. To evaluate the importance of these and other amino acids in the leader peptides of archaeal flagellins for processing by a peptidase, Methanococcus voltae mutant FlaB2 preflagellin genes were generated by PCR and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…Although the overall leader sequence is not highly conserved, a net positive charge is present, and the three amino acids preceding the cleavage site tend to be KKG, KRG, or RRG. It has been demonstrated that a positively charged amino acid at position Ϫ2 and a small amino acid (glycine or alanine) at position Ϫ1 are important for preflagellin processing in M. voltae (46). Furthermore, that study identified other amino acids involved in processing that are also found in the flagellins identified in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Although the overall leader sequence is not highly conserved, a net positive charge is present, and the three amino acids preceding the cleavage site tend to be KKG, KRG, or RRG. It has been demonstrated that a positively charged amino acid at position Ϫ2 and a small amino acid (glycine or alanine) at position Ϫ1 are important for preflagellin processing in M. voltae (46). Furthermore, that study identified other amino acids involved in processing that are also found in the flagellins identified in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Jarrell and colleagues (19) suggested that the archaeal type IV prepilin-like signal peptidase homologs are in fact preflagellin peptidases, i.e., enzymes with a dedicated role in the processing of flagellin precursors. According to these authors' hypothesis, other pro- (41). However, S. solfataricus PibD seems to be equipped with a much broader specificity.…”
Section: Discussionmentioning
confidence: 98%
“…However, S. solfataricus PibD seems to be equipped with a much broader specificity. It processes preGlcS*, even though the signal sequence lacks a lysine or arginine at position Ϫ3, whereas an M. voltae flagellin mutant with alanine or glutamate at the same position was cleaved only partially (41). Moreover, a lysine-to-alanine mutation of the GlcS* signal sequence at position Ϫ2 did not affect the cleavage reaction, and glycine at position Ϫ1 could be changed to alanine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Archaeal flagellins are more similar to T4 pilins than to eubacterial flagellins, including a requirement for processing of their type III secretion signal by dedicated peptidases prior to assembly (388). However, archaeal flagellar filaments are functionally similar to bacterial flagella, providing a propulsive force through rotation, rather than retraction, of the fibers.…”
Section: Motilitymentioning
confidence: 99%